ANALISIS KOMPARASI KUALITAS LABA SE BELUM DAN SESUDAH PENERAPAN STANDAR PELAPORAN KEUANGAN INTERNASIONAL (IFRS) PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Yunita -; Zulbahridar -; Al Azhar Lukman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research is to give empiris about comparation analyze of earnings quality before and after adoption of the international financial reporting standart. Main variable in this research is International Financial Reporting Standart (IFRS) and Earnings Quality. This research also use some free variable as Earning Management, Earning Persistence, also Profitability Ratio (Net Profit Ratio, Gross Profit Ratio and Operating Profit Ratio). Earnings Management refers to intervention to extern Financial Statement to get own profit. Earnings Persistence refers to expected future earning that implicated by current year earning . Net profit Ratio refers as comparison between net profit and sales. Gross Profit Ratio refers to comparison between gross profit and sales. Operating profit Ratio refers to comparison between operating profit and sales.This research used sample of manufacturing company that listed in BEI for four years (2010-2013). This research used convenience sampling method. Research Tool used secondary .This research data using Paired T-Test by SPSS (Statistic Product and Service Solution) 22. The result of this research showed that comparison analyze from variable- variable Earnings Management, Earnings Persistence, Net Profit Margin Ratio, Gross Profit Margin Ratio and Operating Profit Margin Ratio before and after adoption IFRS has no difference at all.Keywords: IFRS, Earning Quality, Earning Management, Earning Persistence, Profitability Ratio.